(3QSGdI eKdG UQjI HYV MceGA GdOjGQ JhHjNkG def bUQ Yf MaX GdCeGfIs - (3jMji Hf MeRI Hf Ydj Hf EHQGgje, GdMSjfj GdYdhqj GdWGdHj , GdeDjO HGddg , J (B745 (3g`s
(3ChdgG (B:s
(3HSe Edg GdMb hehdi GdNdb hPcQ SajfI GdfLGI hCUZQ GdOYGI Cf Mcje GdOgQ Cee SaQG hcGf ai MceJg eSJhQkG s
(3BNQgG (B:s
(3agPG GdeKd ddfahS GdWGgQI OhGA hTaGA hddfahS GdLGgdI hdg GdCYXGe hGdELdGd hGdJbOjS hGdJSHjM s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B43s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
Keywords: (3abg GdePGgH GdCNQis